2020
DOI: 10.1111/bcp.14254
|View full text |Cite
|
Sign up to set email alerts
|

Metamizole: An underrated agent causing severe idiosyncratic drug‐induced liver injury

Abstract: Drug-induced liver injury (DILI) is a heterogenous entity leading to liver damage. We have analysed the frequency, biochemical and histological patterns and clinical courses of DILI cases due to metamizole at our tertiary care centre in Hamburg, Germany.Methods: Consecutive patients with DILI who presented to our clinic were analysed retrospectively. Causes of acute hepatitis other than DILI were excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
3
38
0
2
Order By: Relevance
“…Causality assessment was supported by the MH cell test, for which a sensitivity and specificity of 92% and 100%, respectively, have been shown previously in a selected cohort of DILI patients with positive rechallenge. 10 In accordance with Sebode et al, 5 we observed a hepatocellular phenotype in most cases. The median latency between initiation of metamizole therapy and onset of liver injury was 52 days, and median average daily dose was 1000 mg.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Causality assessment was supported by the MH cell test, for which a sensitivity and specificity of 92% and 100%, respectively, have been shown previously in a selected cohort of DILI patients with positive rechallenge. 10 In accordance with Sebode et al, 5 we observed a hepatocellular phenotype in most cases. The median latency between initiation of metamizole therapy and onset of liver injury was 52 days, and median average daily dose was 1000 mg.…”
supporting
confidence: 91%
“…In conclusion, as part of our prospective study on the hepatotoxic potential of drugs, we identified 10 patients with metamizole-induced DILI, who presented with a similar pattern as the previously described cases. 1,5 Metamizole was the most likely causative agent with RUCAM scores of 6 to 9 and a positive rechallenge in 40% of the cases. We therefore support Björnsson's statement that the hepatoxic potential of metamizole has been clearly demonstrated by now.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the extensive hepatic metabolism of metamizole, mainly mediated by cytochrome P450 [5], its lipophilicity and the relatively high daily dose, all of which are known risk factors for druginduced liver injury (DILI) [6,7], it is surprising that the hepatotoxic potential has not been a topic for pharmacovigilance until now. Interestingly, Sebode et al reported 23 cases of metamizole-induced DILI recently, which corresponded to 15% of all the DILI cases included in their centre [8]. The majority of the cases presented with a hepatocellular type of injury, nearly 50% of patients fulfilled Hy's law criteria, meaning alanine aminotransferase (ALT) > 3 × the upper limit of normal (ULN) and total bilirubin (TBIL) > 2 × ULN, and 9% of the patients developed ALF [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sebode et al reported 23 cases of metamizole-induced DILI recently, which corresponded to 15% of all the DILI cases included in their centre [8]. The majority of the cases presented with a hepatocellular type of injury, nearly 50% of patients fulfilled Hy's law criteria, meaning alanine aminotransferase (ALT) > 3 × the upper limit of normal (ULN) and total bilirubin (TBIL) > 2 × ULN, and 9% of the patients developed ALF [8].…”
Section: Introductionmentioning
confidence: 99%